Disparity in Judges' Considerations in Divorce Suits Due to Lack of Support (Study of Decisions No. 130/Pdt.G/2026/PA.Wsb and No. 95/Pdt.G/2026/PA.Wsb) - Mukhammad Khabibullah Idris (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2026)
This study examines the disparity of judges' legal reasoning in divorce lawsuits due to lack of maintenance, focusing on Decision Number 130/Pdt.G/2026/PA.Wsb and Decision Number 95/Pdt.G/2026/PA.Wsb at the Religious Court of Wonosobo. The problem addressed is the inconsistency in interpreting the element of “failure to provide maintenance,” which leads to different legal constructions despite similar grounds of claim. This research employs a qualitative method with a normative juridical approach using secondary data, including court decisions, statutory regulations, and relevant literature. The analysis uses a comparative descriptive method based on the theory of legal certainty, justice, and expediency. The findings reveal that both decisions consider philosophical, juridical, and sociological aspects; however, they differ in legal reasoning. Decision Number 130 emphasizes the violation of taklik talak and applies khulu' with compensation, while Decision Number 95 focuses on continuous marital conflict and results in talak ba'in sughra. These differences indicate that judges exercise discretionary power in interpreting legal norms based on factual circumstances, particularly regarding the duration and impact of neglect. Consequently, such disparities affect legal certainty and the level of protection afforded to wives. The study concludes that clearer parameters are needed in assessing “failure to provide maintenance” to ensure consistency, fairness, and stronger legal protection within the religious court system.